A miniature biomimetic sonar and movement tag to study the biotic environment and predator-prey interactions in aquatic animals. (June 2019) - Goulet, Pauline; Guinet, Christophe; Swift, René; Madsen, Peter T.; Johnson, Mark
Abstract: How predators find, select and capture prey is central to understanding trophic cascades and ecosystem structure. But despite advances in biologging technology, obtaining in situ observations of organisms and their interactions remains challenging in the marine environment. For some species of toothed whales, echoes from organisms insonified by echolocation clicks and recorded by sound logging tags have provided a fine-scale view of prey density, and predator and prey behaviour during capture attempts, but such information is not available for marine predators that do not echolocate. Here the development and performance of a miniature biomimetic sonar and movement tag capable of acquiring similar data from non-echolocating marine predators is reported. The tag, weighing 200 g in air, records wide bandwidth sonar data at up to 50 pings a second synchronously with fast-sampling sensors for depth, acceleration, magnetic field and GPS. This sensor suite enables biotic conditions and predator behaviour to be related to geographic location over long-duration foraging trips by apex marine predators. The sonar operates at 1.5 MHz with a 3.4° beamwidth and a source level of 190 dB re 1 μPa at 1 m. Sonar recordings from a trial deployment of the tag on a southern elephant seal contained frequent targets corresponding to small organisms up to 6 m ahead of the tagged animal. Synchronously sampled movement data allowed interpretation of whether the seal attempted to capture organisms that it approached closely while the high sonar ping rate revealed attempts by prey to escape. Results from this trial demonstrate the ability of the tag to quantify the biotic environment and to track individual prey captures, providing fine-scale information on predator-prey interactions which has been difficult to obtain from non-echolocating marine animals. Highlights: Simultaneous observations of predators and prey are challenging in the ocean. We developed a miniature 200 g low-power sonar and movement tag to study foraging. The tag combines a 1.5 MHz short-range sonar with GPS and high-rate motion sensors. Continuous operation for one month and ping rates up to 50 Hz are supported. The tag recorded organism abundance and detailed predator-prey interactions on a seal.